A modified strain-controlled reference stress approach for submarine pipelines under large-scale plastic strain. (May 2018) - Zhao, Xiaoxin; Xu, Lianyong; Jing, Hongyang; Zhao, Lei; Huang, Jiangzhong
Highlights: Reference stress approach cannot be applied directly to submarine pipelines under strain-controlled conditions. The nominal stress was acquired using the derived implicit equation, f ( σn, εn ) = 0, according to the relationships among the true stress, true strain, nominal stress, nominal strain, and Ramberg–Osgood's constitutive model. Therefore, the input parameter P in reference stress approach can be acquired through the implicit equation. Reference stress approach comes from EPRI approach by the assumption that h ( n ) =  h (1), and this will sacrifice the accuracy. A γ factor was used to modify the limit load solution in order to increase the accuracy. A regression analysis of γ based on finite element analysis was executed. The reference stress approach was modified through γ factor and the empirical formula of γ was acquired. Results of the modified reference stress approach through γ proved to be more close to FEA. Abstract: The reel-lay approach is widely applied in submarine pipelines. During the process of reeling and unreeling, pipelines are subjected to nominal strain of 1–4%. In this study, various pipeline geometries and crack dimensions were calculated using a finite element analysis and analytical solution under strain-controlled boundary conditions. A modified reference stress approach was applied under strain-controlled boundary conditions using a derived implicit analytical solution of the nominal stress. The limit load solution was modified through a γ factor based on the finite element analysis under strain-controlled boundary conditions. A regression analysis of γ was conducted and an empirical formula was determined. The modified strain-controlled reference approach is in contrast to other ECA methods and proved to be closer to the finite element analysis results.